Paciente de sexo femenino de 31 años con hepatitis A - Foyain Peñafiel, Gabriella Naomi (2019)
The present case concerns a female patient of 31 years of age, who weighs 69 kg and a height of 1.54 m, comes to the clinic for pain in the right hypochondrium, malaise, fever, choluria, nausea and vomiting. The medical diagnosis of viral hepatitis A was positive. It is derived to the nutritionist so that it is valued by anthropometric, biochemical, clinical and dietary measures, it will be followed up and a food plan will be elaborated and nutritional status will be improved, providing the necessary nutrients for daily consumption, indicating which are the recommendations to follow and correct your lifestyle